The Politics of Azusa: Transforming Citizenship at the Margins - Day, Keri L. (Political theology, 2021)
The Azusa Street revival of 1906 is one of the most important revivals in early Pentecostalism and offers resources in rethinking the Christian political imagination. I want to offer sustained reflection of this revival, as it resignifies the nature of what is political. I argue that Azusa embodied a non-statist idea of the citizen, encouraging radically inclusive practices of political belonging. Members of Azusa did not trust the institutional logic of the modern state, as Azusa believed that white supremacy over-determined the American state. This paper explores how Azusa challenged American democracy and its statist idea of the citizen-subject, as this political idea created the very conditions of black subjugation. Examining how Azusa rejects the statist idea of the citizen, this paper reflects on questions of the democratic, moral and political agency, citizenship, and political belonging. This paper poses questions such as: Why is it essential to foreground forms of political agency that are not in service to the state? What is the shape of the democratic in light of non-statist political practices? What does Azusa’s ecclesial life teach us about political practices of human belonging?